DEVELOPMENT OF EDUCATIONAL ENTREPRENEURSHIP LEARNING E-BOOKLETS - Sihaloho, Fahmi Ashari S.; Pratikto, Heri; Churiyah, Madziatul (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
The purpose of this research is to produce an e-Booklet based on Project Based Learning in the Education Entrepreneurship course. The research method used is the ADDIE development model which has five fundamental stages, namely: (A) analysis, (D) Design, (D) Development, (I) Implement, (E) Evaluation. The findings of this study were successful in developing project based learning e-Booklets in the Educational Entrepreneurship Course. It is believed that the developed E-Booklet has been effective based on the results of interviews and discussions with students. The implication of this research is that the e-Booklet can be developed on other materials and subjects to be able to develop students' interest in learning.